Coating solidification mechanism during plasma-sprayed filling the laser textured grooves. (October 2019) - Yi, Peng; Jia, Delong; Zhan, Xianghua; Xu, Pengyun; Mostaghimi, Javad
Highlights: The quadric parabola topography was extracted from the groove profile of laser texture for modeling. The solidification mechanism and air entrainment of plasma sprayed filled textured molybdenum coatings were investigated. The bonding mechanism of filling molybdenum coating and texture groove substrate was studied. Abstract: The AISI 304 L stainless steel substrate was treated by laser surface texture to obtain texture groove widths and depths of 60 and 50 μm, respectively. Molybdenum coating was deposited on the substrate by atmospheric plasma spraying. 3D surface topography instrument was used to extract the groove profile, and MATLAB was utilized to fit the quadratic parabola to develop a texture groove model. A commercial software-based volume of fluid method is developed to 3D simulate the single groove multi-droplet filling. The simulation parameters were determined experimentally, in which the droplet diameter, impact velocity, initial droplet, and substrate temperature were 50 μm, 60 m/s, 2800 °C, and 25 °C, respectively. The solidification mechanism of the filling coating in the substrate groove was investigated. The cross-sectional morphology and element distribution of the filled coating were characterized by scanning electron microscopy and energy dispersive spectroscopy, respectively. The bonding state and filling quality of the grooved substrate and filling coating were studied. Results showed that the first splat is filled effectively in the texture groove and solidified to form an evident groove shape. The air entrained by the filling coating is mainly distributed in the interfacial and interlamination gap, and its content is high when it is close to the edge. The filling coating and substrate in the groove are a combination of mechanical and metallurgical bonding.